2008
DOI: 10.2172/939847
|View full text |Cite
|
Sign up to set email alerts
|

The Sandia MEMS Passive Shock Sensor : FY08 failure analysis activities.

Abstract: This report summarizes failure analysis activities performed on various designs of the MEMS based Passive Shock Sensor (PSS). The failure analysis activities in this report focus on identifying root cause of failures observed at both die and package levels. The findings from these failure analyses have and will lead to implementation of corrective actions focusing on maturing the MEMS-based PSS and meeting product deliverables and milestones.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Unfortunately, the dimples were the likely cause of a new failure mode -sliding friction due to closure of the dimple gap. While several factors are likely contributors to the gap closure failure, detailed analysis [Walraven et al 2008] has shown that the gap spacing fabricated was smaller than the design specification. Overall, the gap closure was most likely a result of a combination of factors including gap spacing (fabrication out of spec), deflection of the device out-of-plane either before or during a shock event, and possibly bowing of the mass structure due to stress gradient through the mass thickness.…”
Section: Revisionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unfortunately, the dimples were the likely cause of a new failure mode -sliding friction due to closure of the dimple gap. While several factors are likely contributors to the gap closure failure, detailed analysis [Walraven et al 2008] has shown that the gap spacing fabricated was smaller than the design specification. Overall, the gap closure was most likely a result of a combination of factors including gap spacing (fabrication out of spec), deflection of the device out-of-plane either before or during a shock event, and possibly bowing of the mass structure due to stress gradient through the mass thickness.…”
Section: Revisionmentioning
confidence: 97%
“…The thicker polysilicon proved to be a difficult process change that resulted in unforeseen problems (see the failure analysis report [Walraven et al 2008]). However, we were able to qualitatively test the strength of the nitride isolation layer, which became a major focus of Revision 7.…”
Section: Revisionmentioning
confidence: 99%